1998
DOI: 10.1016/s0014-5793(98)01510-5
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum‐free nitrate reductases from vanadate‐reducing bacteria

Abstract: Two catalytically distinct molybdenum-free dissimilatory nitrate reductases, a soluble periplasmic and a membranebound one, were isolated from the vanadate-reducing facultatively anaerobic bacterium Pseudomonas isachenkovii and purified to electrophoretic homogeneity. The enzymes did not contain molybdenum, the periplasmic enzyme contained vanadium, whereas the membrane-bound enzyme was vanadium-free. Both nitrate reductases lacked molybdenum cofactor. This fact was proved by reconstitution of the apoprotein o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…Catalytic activi ty of the individual subunits of molybdenum containing nitrate reductases has not been yet described. We have pioneered in describing catalytic activity of monomeric molybdenum free nitrate reductases [11,21,22]. An abil ity of the nitrate reductase from Halomonas sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalytic activi ty of the individual subunits of molybdenum containing nitrate reductases has not been yet described. We have pioneered in describing catalytic activity of monomeric molybdenum free nitrate reductases [11,21,22]. An abil ity of the nitrate reductase from Halomonas sp.…”
Section: Resultsmentioning
confidence: 99%
“…Toxic metals or other stress factors can induce the replace ment of molybdenum in the active enzyme center by other metals or trigger the synthesis of isofunctional enzymes encoded by distinct genes. From the vanadate reducing bacterium Pseudomonas isachenkovii we have isolated two catalytically distinct molybdenum and molybdocofactor free dissimilatory nitrate reductases (periplasmic and membrane bound, respectively) [11], which suggests the occurrence of "alternative" nitrate reductases lacking molybdocofactor in their active centers.The goal of this study was to investigate a nitrate reductase from the haloalkalophilic denitrifying bacteri um Halomonas sp. strain AGJ 1 3 isolated from the Naiwasha soda lake in Kenya.…”
mentioning
confidence: 94%
“…Some recent studies have reported that the reduction of many metals and metalloids are related to nitrate reductase. Antipov et al (2000) have found that V(V) reduction follows nitrate consumption, and that the process is associated with some structural reorganizations of nitrate reductase. Rege et al (1999) have reported that selenate and selenite reduction occurs after a lag period, during which a seleniumreducing population was stimulated or the needed enzyme was produced in the existing denitrifying population.…”
Section: Discussionmentioning
confidence: 99%
“…The recent report of two molybdenum-free nitrate reductases from the vanadate-reducing bacterium Pseudomonas isachenhovii (Antipov et al 1998) suggests that alternative pathways for nitrate reduction may exist. The periplasmic nitrate reductase contains vanadium, whereas no metals have been found in the membrane-bound nitrate reductase (Antipov et al 1998).…”
mentioning
confidence: 99%
“…The periplasmic nitrate reductase contains vanadium, whereas no metals have been found in the membrane-bound nitrate reductase (Antipov et al 1998). The conclusion that the enzyme complex from G. metallireducens does not contain molybdenum is based on the metal analyses and is supported by the inhibition studies.…”
mentioning
confidence: 99%